Benefits of Pseudomonas poae s61 on Astragalus mongholicus growth and bioactive compound accumulation under drought stress. Issue 1 (1st January 2019) - Sun, Haifeng; Kong, Liuli; Du, Huizhi; Chai, Zhi; Gao, Jianping; Cao, Qiufen
ABSTRACT: The aim of this study was to explore the beneficial effects of endophytic Pseudomonas poae strain S61 on medicinal plant Astragalus mongholicus. Growth and production of indoleacetic acid (IAA) of the strain was firstly characterized under stress conditions, demonstrating that the strain performance was more robust in the medium containing 20% PEG6000. Beneficial effects of the strain on host seedlings were then investigated by pouring 20% PEG6000 for 3 weeks to mimic drought stress. Among growth parameters, root biomass and root-shoot ratio were significantly enhanced by the combination of 20% PEG6000 with the strain inoculation while the individual trial had no effect. The combination trial also increased calycosin-7-O-glucoside and ononin accumulations in the roots, suggesting that the strain executed beneficial effects on A. mongholicus only when it grew under drought stress. Using MDA as lipid peroxidation parameter, our result indicated that leaf lipid peroxidation should be involved in the process.